Analisis Manajemen Keselamatan Kebakaran Gedung Berbasis Metode Penilaian Keandalan Sistem Keselamatan Bangunan pada Gedung Green House Display – Badan Riset dan Inovasi Nasional Cibinong Kabupaten Bogor - Nurjaman, Aceng Galih; Azhar, Moh (Universitas Ibn Khaldun, 2024)
Abstract: The Green House display building is an exhibition building of living plants from various mountains in Indonesia including the mountains of Java, the mountains of Sumatra, the mountains of Kalimantan, and the mountains of Papua. This building is the only building in Indonesia, which presents the atmosphere of the mountains exactly the same as the original mountains, both plants, soil and air temperature, but is in a closed room. This building is very prone to fire because there are so many flammable materials such as leaves, wood and others. Therefore, the application of Building Fire Safety Management in this building must be applied as well as possible. To analyze the above, an inspection of the building's fire safety system equipment will be carried out for compliance with applicable regulations. The analysis will be carried out by checking directly and participating in tests or tests on the function of the installed fire protection system. The inspection and testing of the fire safety system in question includes: checking the completeness of the fire protection system, checking the use of fireproof materials, checking the provision of evacuation route access and checking the reliability of fire safety. Based on the results of the inspection and tests, it can be concluded that based on NFPA standards and the Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia No: 4/MEN/1980, yard hydrant equipment and Light Fire Extinguishers in the Green House Display building, still do not meet the requirements, but for the use of building materials in this building, almost all of them can be categorized as building materials that are quite resistant to fire/not flammable. For access to fire safety facilities/evacuation routes in this building is well installed and the radius of coverage is in accordance with the Indonesian Minister of Health Regulation number 48 of 2016, which is a maximum of 45 meters between emergency stairs. As for the reliability of the building safety system in this building, it can be categorized as